Orthophoto mapping: A fundamental data layer for urban GIS in NGII in Nepal (Journal on Geoinformatics, Nepal, 2003)
More recently, a national geographic information infrastructure programme to support spatial data need of different users has been initiated in Nepal. Quite often, urban planners need very detailed topographic details for their applications and more often they need a temporal coverage of data. Line map data layer having a clean topological vector database have very easy applications in a GIS, but they cannot fulfill many of the urban planning needs. To cater for these needs, an orthophoto map layer in the Nepalese NGII is under progress. The rationale and the coverage of the current orthophoto-mapping programme have been explained. A suggestion for a temporal coverage of orthorectified high resolution remote sensing imagery has been suggested.